Uma abordagem do sistema caótico em circuitos elétricos usando simulação no ensino médio - Marinho, Lucas Linhares (2020)
The present work highlights the study on the approach of the chaotic system involved in non-linear electrical circuits in didactic activities in the teaching of Physics, in High School, through online simulations of the applet type. The objective of this research was to apply a non-linear system to the circuits and their related equations to then analyze and verify their behavior, a subject that is part of the 2nd part of Physics 03 in High School and which are studied in the 3rd year in Electricity, in a more dynamic, profitable, contextualized way and with the aid of an online simulator, free of charge and open access. It is worth mentioning that an important detail in this work was to insert the content of the chaotic system, a subject that is not even seen in undergraduate courses. This is the differential of the work, incorporating content that is not inserted in the curriculum of High School, but the intention here is only to contextualize it within the electrical circuits and show the importance of it using simulations to better understand them. The simulations were approached by a simulator called Falstad that served as a resource used as a strategy to mediate the teaching of electrical circuits involving chaotic system and make learning more effective and active through graphics and mathematical modeling from the virtual simulator. The activities proposed in this research were based on the constructivist theory of Jerome Bruner that takes into account teaching by discovery and the proposal for a curriculum in a spiral format, in which the content is proposed in a superficial and in-depth way according to the student's learning. As a tool for data collection, a questionnaire was used as a diagnosis on the subject at hand, a pre-test to measure knowledge about the issues involved, a list of activities based on the outline of the class and a post-test as an evaluation. It can be seen that from the proposed methodology taught in schools, it was obtained from the students' view that it shortened doubts and was a potentially significant methodology and using the simulations, experiment and the physical concepts already clarified, and thus, approached theoretical and scientific knowledge of Physics with the student's reality, favored their learning, connections between problem situations presented in virtual simulations and physical contents were obtained through interaction and direct contact, aroused the pleasure of learning and activities, and had an innovative character, making Physics classes more profitable.